2016
DOI: 10.1016/j.ajic.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on indwelling urinary catheter use in the hospital

Abstract: Urinary tract infections are one of the most common hospital-acquired infections, with 70%-80% resulting from catheter-associated urinary tract infections (CAUTIs). We undertook a qualitative study to assess patient perspectives of indwelling urinary catheters using a semistructured interview. We found that patient awareness and patient engagement regarding indwelling urinary catheters and their consequences could be improved in the hospital setting. Implementing educational programs incorporating patient pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 10 publications
0
21
0
3
Order By: Relevance
“…These observed positive perceptions are likely related to lack of knowledge of urinary catheters, their risks, and alternative methods. In a recently published study in a separate cohort, our group found that 15 of 20 adult patients with indwelling urinary catheters perceived they had not received adequate education about catheters—all of these patients felt alternative methods of excretion were not discussed and a large proportion (65% [13/20]) felt they had not received sufficient information on urinary catheter risks 6 . The work presented here confirms these results in a different patient population using a theoretical framework, finding most patients reporting little or no education on catheters (63%) or alternative methods (87%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These observed positive perceptions are likely related to lack of knowledge of urinary catheters, their risks, and alternative methods. In a recently published study in a separate cohort, our group found that 15 of 20 adult patients with indwelling urinary catheters perceived they had not received adequate education about catheters—all of these patients felt alternative methods of excretion were not discussed and a large proportion (65% [13/20]) felt they had not received sufficient information on urinary catheter risks 6 . The work presented here confirms these results in a different patient population using a theoretical framework, finding most patients reporting little or no education on catheters (63%) or alternative methods (87%).…”
Section: Discussionmentioning
confidence: 99%
“…Our group recently published a pilot study examining patient perceptions of urinary indwelling catheters. 6 Here, we expand upon this work in a different patient population using a formal theoretical framework to identify key themes. The Health Belief Model (HBM) framework emphasizes perceptions of susceptibility, benefits and barriers, and "cues to action" (Figure 1), and has been used to study patient compliance and patient decisionmaking.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Safdar ve arkadaşlarının kalıcı idrar sondası kullanımına ilişkin hasta görüşlerini inceledikleri çalışmada da benzer şekilde hastaların %65'inin kalıcı üriner kateter bulundurma riskinin kendilerine açıklanmadığı belirtilmektedir. 13 Çalışmanın sonucunda hastaların çoğunluğunun idrar torbasının nerede durması gerektiğini bilmediği belirlendi. Bu konuda hasta görüşlerini inceleyen çalışma sonucuna ulaşılamamasına rağmen, McNulty ve arkadaşlarının 14 yaptıkları çalışmada hemşirelerin %96'sının idrar torbasını yatak kenarına astıkları, Çelik ve arkadaşlarının 15 yaptıkları çalışmada ise hemşirelerin drenaj sisteminin yere temasını önlemede bilgi düzeylerinin yüksek olduğu belirtilmiştir.…”
Section: Bulgularunclassified
“…Quast ve arkadaşlarının 12 sağlık inanç modeli doğrultusunda kalıcı üriner kateteri olan hastaların algılarını anlamak amacıyla yaptıkları çalışmada hastaların %63'ünün kateterle ilgili hiçbir eğitim almadığı belirtilmiştir. Safdar ve arkadaşlarının kalıcı idrar sondası kullanımına ilişkin hasta görüşlerini inceledikleri çalışmada da benzer şekilde hastaların %65'inin kalıcı üriner kateter bulundurma riskinin kendilerine açıklanmadığı belirtilmektedir 13. Çalışmanın sonucunda hastaların çoğun-…”
unclassified